Modulation of orbitofrontal-striatal reward activity by dopaminergic functional polymorphisms contributes to a predisposition to alcohol misuse in early adolescence - Baker, Travis E.; Castellanos-Ryan, Natalie; Schumann, Gunter; Cattrell, Anna; Flor, Herta; Nees, Frauke; Banaschewski, Tobias; Bokde, Arun L.W.; Whelan, Rob; Buechel, Christian; Bromberg, Uli; Orfanos, Dimitri Papadopoulos; et al. (Cambridge University Press, 2018)
Background: Abnormalities in reward circuit function are considered a core feature of addiction. Yet, it is still largely unknown whether these abnormalities stem from chronic drug use, a genetic predisposition, or both.